2010
DOI: 10.1016/j.placenta.2010.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The levels of hypoxia-regulated microRNAs in plasma of pregnant women with fetal growth restriction

Abstract: MicroRNAs (miRNAs) are short non-coding RNAs that regulate gene expression at the post-transcriptional level. While mostly intracellular, a portion of cellular miRNAs is released to the circulation and their level in the plasma is altered in certain pathological conditions such as cancer, and also during pregnancy. We examined the circulating levels of a set of trophoblastic miRNAs, which we recently found to be regulated by hypoxia, in the plasma of pregnant women with fetal growth restriction. As expected, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(121 citation statements)
references
References 42 publications
5
114
1
1
Order By: Relevance
“…Interestingly, many of these miRNAs, including members of the C19MC, are found in the maternal blood throughout pregnancy and rapidly decline in the first 24 h postpartum (19,20), suggesting a miRNA-based mechanism for fetal-maternal communication (13,21). Our data thus provide evidence for a unique paracrine and/or systemic function of placental trophoblasts, using exosome-mediated transport of a unique set of primate-specific effector miRNAs to directly communicate with maternal cells and possibly neighboring placental cells and regulate their immunity to viral infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, many of these miRNAs, including members of the C19MC, are found in the maternal blood throughout pregnancy and rapidly decline in the first 24 h postpartum (19,20), suggesting a miRNA-based mechanism for fetal-maternal communication (13,21). Our data thus provide evidence for a unique paracrine and/or systemic function of placental trophoblasts, using exosome-mediated transport of a unique set of primate-specific effector miRNAs to directly communicate with maternal cells and possibly neighboring placental cells and regulate their immunity to viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…The human C19MC is the largest known miRNA cluster, comprising 46 miRNAs that are highly expressed almost exclusively in the human placenta. Moreover, as a group, C19MC miRNAs are also the most abundant miRNA species in trophoblastic exosomes, with a strong correlation between C19MC miRNA levels in PHT cells and in PHT-derived exosomes (4,5,8,13). To date, the function of these miRNAs has remained elusive.…”
Section: Pht-derived Exosomes Protect Recipient Cells From Viral Infementioning
confidence: 99%
“…Specific expression of miRNAs might correlate with particular human tumour phenotypes and biological characters such as response to treatment and prognosis [14][15][16]. Recent studies have indicated that serum and plasma contain high levels of stable miRNAs, and the expression profile of these miRNAs has shown great promise as a novel non-invasive biomarker for thediagnosisofcancerandotherdiseases [17][18][19].…”
Section: Patient Treatment and Assessmentmentioning
confidence: 99%
“…Further research demonstrated that chorionic villous trophoblasts continuously released placenta-specific miRNAs into maternal circulation via exosomes (52). The level of expression of placenta-specific miRNAs in maternal peripheral blood is closely related to pre-eclampsia (PE) (3), congenital heart defects (CHD) (53), and fetal growth restriction (54).…”
Section: Resultsmentioning
confidence: 99%